The Influence of Continental Mixosedimentite Sedimentation on Shale Oil Sweet Spot: A Case Study on the Permian Lucaogou Formation in the Jimsar Sag of the Junggar Basin, NW China - Liang, Chenggang; Zhang, Jinfeng; Zhu, Jianjun; Wang, Wei; Guo, Haiping; Tan, Qiang; Zhao, Jun; Luo, Hongcheng (Frontiers in Earth Science, 2023)
Over the years, shale oil has been at the leading edge of oil exploration and also become the hotspot of reserve increases for various oil fields. The Permian Lucaogou Formation in Jimsar Sag has been less extensively researched in terms of, among others, lithologic interpretation of fine-grained mixosedimentite, identification and classification of sedimentary microfacies, sweet spot evaluation. The present study identifies the classification of sedimentary microfacies, characteristic distribution of sedimentary reservoir and spatial configuration distribution of facies-controlled sweet spot body based on core logging, cutting logging and data while drilling, combined with logging information, experimental analysis data and production data with respect to formation test and production test and through the lithology identification based on element logging. This study indicated: (1) Microfacies of the reservoir body include shallow lacustrine sand bar, mixing beach and dolomitic flat. Different microfacies are adapted to different lithologies or lithological association. (2) The lower sweet spots P2l12-3, P2l12-2 and P2l12-1 are evolved into dolomitic flat from mixing beach from NE to W. And dolomitic flat is mostly developed in the west of work area and mixing beach better developed in the east. Shallow lacustrine sand bar is highly developed in the middle location, and mixing beach and shallow lacustrine sand bar are highly developed in the northern and southern sides. (3) Sedimentary microfacies have evident controls over sweet spots. The upper sweet spots P2l22-3 and P2l22-2 are dominated by Class I sweet spots followed by Class II and IV sweet spots, which are major sweet spot reservoirs. The upper sweet spot P2l22-1 is mainly suffused with Class IV sweet spots, and Class I reservoir is feldspathic litharenite (shallow lacustrine sand bar microfacies accordingly).